Military intervention in the 1990s : a new logic of war - Connaughton, R. M. (Richard Michael), 1942- (Operational level of war., 1992)
By considering the operational factors involved in all types of intervention, and by examining some of the historical precedents for these operations, Richard Connaughton provides a timely interpretation of international affairs.